Effectiveness of "SAFETYPOLY" Learning Media in Improving Public Knowledge of Chemical Hazards in the Printing Industry - Zahra, Alya Sofia; Purboeningrum, Amanda Desti; Mahartiko, Ardheta Heru; Anisa, Aza Putri; Fitriana, Della Rizky; Karimah, Safrina Azwa (Journal of Safety Education, 2024)
In today's development, many games are played by all groups, from small children to adults and older people. This game can be used for fun or as a learning medium. This game can also be used to increase public knowledge, one of which is regarding occupational safety and health. There is a game that can be used to improve understanding in society, namely monopoly. Therefore, this research aims to determine the effectiveness of monopoly learning media, which contains occupational safety and health "safetypoly", in increasing public knowledge regarding Occupational Safety and Health. This study used a quantitative research approach with a pre-experimental type of research. The research design used in this study was the One Group Pretest-Posttest Control Design. Data collection methods include questionnaires, observation, and interviews. The data analysis methods used in this research are the Validity Test, Reliability Test, Normality Test, and Wilcoxon Test. The "Test Statistics" output is known as Asymp based on the research results.Sig. (2-tailed) is worth 0,000. The value of 0.000 is smaller than <0.05, so there is a difference between the pre-test and post-test results. Apart from that, there was an increase in workers from 20% to 80%. It can be concluded that the safetypoly game influences students' level of knowledge regarding the dangers of chemicals, so this game is effectively used as an educational medium related to occupational safety and health.